Perceived Benefits and Barriers to Chinese COVID-19 Vaccine Uptake Among Young Adults in China - Luo, Wei; Song, Siyu (Frontiers in Public Health, 2022)
Survey-based research has provided us with breadth regarding perceived benefits and barriers to COVID-19 vaccination among Chinese people. Most such research has been conducted within hypothetical COVID-19 vaccine contexts, and few studies are specific to young adults aged 18–40, a pivotal target population for COVID-19 vaccination. Now that the Sinopharm and Sinovac COVID-19 vaccines have been conditionally approved in China, qualitative investigation of young adults' perceptions of benefits and barriers to taking them is warranted. Such research may suggest potential candidate themes in the COVID-19 vaccination promotional messages targeting this population. Through in-depth interviews with 55 Chinese young adults and thematic analysis guided by the health belief model, social benefits and worry reduction emerged as significant positive factors in young adults' intention to vaccinate. Several novel barriers emerged as well, including perceptions that the vaccines' advantages are weak relative to non-medical preventions and beliefs regarding Ti Zhi (the individual human constitution), which confused some participants about their suitability for vaccination. The study also identified two modifying factors, trust in the government and perceived vaccine information insufficiency, both of which appeared to be indirectly associated with vaccination intention by augmenting the perceived barriers. The results suggest that more attention could be paid to young adults' cultural background when developing relevant health communications.